'You feel how you look': Exploring the impacts of unmet water, sanitation, and hygiene needs among rural people experiencing homelessness and their intersection with drug use. - April M Ballard; Hannah L F Cooper; April M Young; Bethany A Caruso (PLOS Water)
Existing literature attests to water, sanitation, and hygiene (WASH) inequities among people experiencing homelessness (PEH) in the United States, but there is a dearth of research on such issues in rural areas. Homelessness is an emerging public health concern in rural areas where homelessness is on the rise, infectious disease outbreaks are becoming increasingly common, and PEH face unique WASH-related challenges compared to their urban counterparts. We conducted an exploratory study to understand the impacts of unmet WASH needs among rural PEH and their intersection with drug use through in-depth interviews (n = 10). Eligible participants were 18 years or older, lived in one of five Central Appalachian counties, and had experienced homelessness in the previous six months. Using thematic analysis, we identified factors that inhibit WASH access, and adverse health and well-being outcomes that result from unmet WASH needs. We also explore how WASH experiences compare among rural PEH who self-reported drug use to those who did not. Our findings revealed that factors at multiple levels inhibited WASH access, including stigma and place-based characteristics, which contributed to the adverse physical, mental, and emotional health of PEH. Comparisons between PEH who used drugs to those that did not revealed the intricate relationship between WASH, homelessness, and substance use in communities impacted by the opioid epidemic. Expanded WASH facilities that are safe and available with no prerequisites can address inadequate access among rural PEH and collaboration with harm reduction services may be advantageous to reach those who inject drugs.